OPTIMIZATION TOURISM VILLAGE SERVICE THOUGHT THE IMPLEMENTATION OF STANDARD OPERATING PROCEDURES IN SUKALAKSANA VILLAGE, SAMARANG, GARUT - Mulyani, Sri; Yuliafitri, Indri (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Sukalaksana, a tourist village in Garut Regency, has great natural and cultural potential, but faces challenges in terms of tourism management and services. One of the main causes is the absence of structured Standard Operating Procedures (SOPs). Through this community service program, a team of students from Padjadjaran University developed and disseminated SOPs to enhance efficiency and service quality in the tourist village. Activities were conducted through observation, interviews, discussions, and training sessions with BUMDes officials and local residents. The results showed increased awareness of the importance of SOPs, improved coordination among management members, and greater community involvement. The implementation of SOPs also supports continuous improvement through a monitoring and evaluation system. This initiative demonstrates that the development and implementation of SOPs can serve as a strategic solution to enhance the competitiveness of tourism villages based on local wisdom.